Comparison of the seismic performance of a continuous bridge using elastomeric and sliding friction type isolators - Trejo-Rodriguez, Cristopher Manuel (2022)
The notable performance of seismically isolated bridges in South America during the last two major seismic events has been reflected in the increase in the use of base insulators in this type of infrastructure. In this work, a multi-span non-isolated bridge was retrofitted to achieve continuous functionality by adopting seismic isolation devices. In order to carry out a comparative evaluation, the bridge was analyzed using elastomeric and sliding type isolation devices. In this case study, the Lead Core Elastomeric Insulator (LRB) and the Triple Pendulum Frictional Insulator (TFPB) were chosen as representative models. For the design of both insulators, it was considered that the values ​​of the isolated periods, the post-yield stiffness and the yield force were similar. This criterion was adopted in order to compare the unique effects of each type of isolator on the seismic response of the bridge. A series of nonlinear dynamic analyzes were performed considering the two components of horizontal ground motion to perform a comparative evaluation. Numerical models were adopted that consider the bidirectional response and describe the different stages of movement of the insulators. Upper and lower limit analyzes were considered to obtain a complete understanding of the response induced by each insulation system. From the results, it is concluded that the LRB system induces a more uniform distribution of seismic forces in the substructure; but experiences greater displacements compared to the TFPB system.